Novel therapy: Combined BRAF and MEK inhibitors for locally advanced BRAF V600L–Positive mucosal melanoma in hypopharynx - Sivakamavalli Jeyachandran (Oral Oncology Reports)
Locoregionally advanced mucosal melanoma, particularly when harboring the BRAF V600L mutation and situated in the hypopharynx, presents a therapeutic challenge due to limited treatment options and aggressive behavior. Traditional modalities often yield unsatisfactory outcomes, prompting the exploration of novel therapeutic approaches. A cutting-edge strategy involves the administration of combined BRAF and MEK inhibitors, targeting specific molecular pathways implicated in mucosal melanoma pathogenesis. BRAF inhibitors, such as vemurafenib and dabrafenib, block mutated BRAF activity, while MEK inhibitors, like trametinib and cobimetinib, target downstream components of the MAPK pathway. This synergistic combination overcomes resistance mechanisms and enhances treatment efficacy. Recent case studies and clinical trials have reported promising results, including improved response rates and prolonged progression-free survival in patients with locoregionally advanced, BRAF V600L–positive mucosal melanoma of the hypopharynx. These findings underscore the potential of combined BRAF and MEK inhibition as a novel therapeutic paradigm for this challenging disease subtype, warranting further investigation to optimize its integration into clinical practice.